Fiber-Chip Bi-Wavelength Multiplexing With Subwavelength Single-Etch Grating Coupler and Diplexer - Lirong Cheng (IEEE Photonics Journal, 2022)
We propose a silicon photonicgrating coupling scheme for dual-band multiplexing in optical fibers. By utilizing subwavelength grating effective refractive index engineering, a dual-band operating grating coupler and a wavelength-polarization diplexer are designed. Both devices are fabricated on a 220-nm silicon-on-insulator and require only one 220-nm full etch step to facilitate cost-effective production. The subwavelength grating coupler guides S-band and O-band lights from a single-mode fiber into a waveguide as transverse-electric and transverse-magnetic modes, while the subwavelength diplexer separates the two signals into two waveguides. Experimentally, our proposed scheme for coupling and multiplexing can achieve a total insertion loss of –4.26 dB at near 1490 nm and –5.86 dB at near 1310 nm.